2018
DOI: 10.1186/s10194-018-0874-y
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA in the treatment of refractory chronic cluster headache

Abstract: BackgroundCluster headache (CH) is a clinically well-defined primary headache disorder, approximately 20% of cluster headache sufferers experience recurrent attacks without periods of significant remission. For the treatment of chronic cluster headache (CCH) only limited therapeutic options are available.MethodsA potential refractory CCH patient group was identified according to the clinical definition of rCCH based on the consensus statement of the European Headache Federation (EHF). Treatment with Onabotulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…A summary of these studies and the main findings are reported in Table 3. In 6 of the longitudinal studies on refractory CCH patients 10,11,15,[24][25][26] and in 3 of the cross-sectional studies, 18,27,28 patients completed the Headache Impact Test (HIT-6). The Migraine Disability Assessment (MIDAS) was used in 2 longitudinal 10,11 and 1 cross-sectional study, 18 the Headache Disability Inventory (HDI) was used in 1 cross-sectional study, 29 and the Pain Disability Index (PDI) was used in 1 longitudinal study.…”
Section: Evaluation Of Disability and Impactmentioning
confidence: 99%
“…A summary of these studies and the main findings are reported in Table 3. In 6 of the longitudinal studies on refractory CCH patients 10,11,15,[24][25][26] and in 3 of the cross-sectional studies, 18,27,28 patients completed the Headache Impact Test (HIT-6). The Migraine Disability Assessment (MIDAS) was used in 2 longitudinal 10,11 and 1 cross-sectional study, 18 the Headache Disability Inventory (HDI) was used in 1 cross-sectional study, 29 and the Pain Disability Index (PDI) was used in 1 longitudinal study.…”
Section: Evaluation Of Disability and Impactmentioning
confidence: 99%
“…In this open-label, non-randomized, single-center study, a greater than 50% reduction in headache minutes was reached in 58.8% of the refractory CCH patients. The pain intensity was also significantly reduced in this patient population [142].…”
Section: Bonta-hemagglutinin Complex Injection Therapy In Chmentioning
confidence: 53%
“…A number of clinical trials using BoNTA-hemagglutinin complex as prophylaxis in CCH patients have been reported [141]; however, only a single trial followed the PREEMPT study protocol until now [142]. In this open-label, non-randomized, single-center study, a greater than 50% reduction in headache minutes was reached in 58.8% of the refractory CCH patients.…”
Section: Bonta-hemagglutinin Complex Injection Therapy In Chmentioning
confidence: 98%
“…Real-world data from headache centers in Italy also support the notion that the benefits of onabotulinumtoxinA treatment using the PREEMPT protocol are sustained, even in patients with a recent onset of CM [28]. Preliminary results also suggest that treatment using the PREEMPT protocol may be beneficial to patients with other chronic, difficult-to-treat headache disorders [29].…”
Section: Discussionmentioning
confidence: 66%